Case Series of Recurring Spontaneous Closure of Macular Hole - Abdelrahman M. Elhusseiny; William E. Smiddy; Harry W. Flynn; Stephen G. Schwartz (Case Reports in Ophthalmological Medicine)
Macular hole can undergo spontaneous reopening and reclosure. This is a retrospective review of three patients who had spontaneous reopening and reclosure of previously spontaneously closed macular hole documented by optical coherence tomography. We report the first case of nivolumab-uveitis-associated macular hole formation. The authors hypothesize that cystoid macular edema (CME) might alter the integrity of foveal tissues or conversely the orientation of the macular hole edges and play a role in formation and resolution of a macular hole.